Система автоматичного управління вікнами та вентиляцією на базі ESP32 - Нго Куок Чієн (ХНУРЕ, 2025)
This work is dedicated to the climate control subsystem for smart home systems designed for small spaces. The key feature of such systems is their optimization, meaning they should manage only the most essential functions. The proposed subsystem is aimed at maintaining normal temperature, humidity, and CO₂ levels. This system can be integrated into larger systems as a subsystem. It can also be expanded by adding additional sensors and actuators.. The main feature of such systems is their optimization, meaning they must manage only the most essential functions. The proposed subsystem is designed to maintain normal levels of temperature, air humidity, and CO₂ concentration. This system can be integrated into other larger systems as a subsystem. It can also be expanded by adding additional sensors and actuators.
Keywords: автоматичне управління вікнами; автоматичне управління вентиляцією